An evaluation of police service delivery to the Mamotintane Community - Khumalo, Bheka Mfundo Hopewell (My University, 2016)
The study focused on Community Policing Forums (CPFs), sector policing and visible policing which are the policing strategies that are currently used to bring police officers closer to the community in order to identify and address the root causes of crime. These strategies are also meant to improve police service delivery which will satisfy and meet the community’s expectations about police services. The study also focused on factors which affect the lack of police service delivery to the community. Quantitative research design was used to evaluate Mamotintane community’s level of satisfaction with police service delivery. Non-probability sampling was used in which purposive or judgmental sampling methodology was used to select the 120 community members from Mamotintane Village. A fixed-response questionnaire that was written in English then translated in Sepedi which is the language commonly used by the target population was used in the study. A Statistical Package for Social Science (IBM SPSS Statistics Version 22) software was then used to analyse the data which was presented in a form of graphs and tables. Summary of the empirical findings are that a large number of 33% community members disagree that CPFs are successfully established in the community where police officers have regular meetings with community members in order to discuss about crimes which are affecting the community. A large number of 43% respondents strongly agree that police corruption has a negative impact to the community.
Thesis (M. A. (Criminology)) -- University of Limpopo, 2016
Keywords: Community Policing Forums; Police service delivery; Sector policing; Visible policing; Police; Community policing -- South Africa -- Limpopo; Law enforcement; Police administration; Crime prevention -- South Africa